Genome-wide responses to shoot nitrate satiety are attenuated by external ammonium in Arabidopsis thaliana. Issue 2 (3rd March 2020) - Hachiya, Takushi; Okamoto, Yuki; Watanabe, Masahiro; Takebayashi, Yumiko; Kojima, Mikiko; Suzuki, Takamasa; Sakakibara, Hitoshi
ABSTRACT: The supply of exogenous nitrate to nitrate-depleted plants transiently changes the expression of nitrate-responsive genes within minutes. In addition to this so-called primary nitrate response, nitrate is suspected to play a long-term regulatory role, acting as a nitrogen (N) status signal for the entire plant. In our recent study using Arabidopsis thaliana, the manipulation of the internal nitrate levels independently of internal organic N without external N indicated that nitrate accumulation in the shoot alone causes genome-wide responses systemically, including the induction of nitrate assimilation genes and repression of N starvation-inducible genes. These responses mimic high nitrate growth situations for plants, suggesting that shoot nitrate acts as a N satiety signal. On the other hand, it is widely known that external supply of ammonium as another major N source also triggers N-rich responses, which led us to hypothesize that the existence of external ammonium may interfere with the genome-wide responses regarding shoot nitrate satiety. To clarify this, we compared transcriptional responses to shoot nitrate satiety with and without external ammonium both in Arabidopsis shoots and roots. Further, in order to determine the major role of nitrate satiety signaling, we extracted those genes regulated by shoot nitrate level regardless of the presence or absence of external ammonium and annotated them by two independent enrichment analyses. Here, we show that genome-wide transcriptional responses to shoot nitrate satiety are significantly lowered in the presence of external ammonium especially in the shoot. A major component for the ammonium-dependent attenuation of the nitrate satiety responses comprised a set of genes encoding the machinery for translation, glucosinolate biosynthesis, and photosynthesis. On the other hand, the nitrate satiety responses commonly observed irrespective of the presence/absence of ammonium included the components for translation and nitrate assimilation, whose transcriptional responses could be mediated partly via NIN-LIKE PROTEIN (NLP), NITRATE-INDUCIBLE GARP-TYPE TRANSCRIPTIONAL REPRESSOR1 (NIGT1), and cytokinin signaling on the basis of our transcriptional profiling and cytokinin determination.